Analisis Manajemen Kas Kecil dalam Laporan Keuangan pada Kantor Pemasaran Perumahan Star Land Regency - Aisyah Brillianta; Dian Fahriani (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The progress of a simple business to a larger stage definitely means the quality of the company's work is good, one of which is the quality of its financial reports. Among the qualities of a good report is cash which is an important part of the company. Petty cash is used by companies to finance expenses/operations whose amounts are relatively small and are not effective if paid by check. Considering the importance of maintaining a petty cash fund for company operational activities. The aim of this research is to review how petty cash is managed and find out the application of petty cash at the Star Land Regency Housing Marketing Office. The research method used in this research is descriptive qualitative with data collection methods using observation methods. The Star Land Regency Housing Marketing Office uses the fluctuation method in recording petty cash in financial reports, namely recording every expenditure that occurs,